2007
DOI: 10.1128/jb.00260-07
|View full text |Cite
|
Sign up to set email alerts
|

Genes, Enzymes, and Regulation of para -Cresol Metabolism in Geobacter metallireducens

Abstract: In aerobic and facultatively anaerobic bacteria, the degradation of para-cresol (p-cresol) involves the initial hydroxylation to p-hydroxybenzyl alcohol by water catalyzed by the soluble, periplasmatic flavocytochrome p-cresol methylhydroxylase (PCMH; ␣ 2 ␤ 2 composition). In denitrifying bacteria the further metabolism proceeds via oxidation to p-hydroxybenzoate, the formation of p-hydroxybenzoyl-coenzyme A (CoA), and the subsequent dehydroxylation of the latter to benzoyl-CoA by reduction. In contrast, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 43 publications
3
65
0
Order By: Relevance
“…The deduced pcmUVWX gene products show similarities to proteins involved in the maturation of molybdenum-containing enzymes and are proposed to play a role in the molybdenum cofactor assembly of 4-hydroxybenzoyl-CoA reductase. On the other hand, the pcmQ gene may encode a MarR-type transcriptional regulator that could be involved in the expression of other pcm genes (277). Proteomic (277) and transcriptomic (48) results have shown that the pcmRST genes are induced not only when the G. metallireducens cells grow in the presence of 4-HBA but also when they are cultivated with benzoate.…”
Section: Gene Clusters For Degradation Of Aromatic Acidsmentioning
confidence: 99%
See 4 more Smart Citations
“…The deduced pcmUVWX gene products show similarities to proteins involved in the maturation of molybdenum-containing enzymes and are proposed to play a role in the molybdenum cofactor assembly of 4-hydroxybenzoyl-CoA reductase. On the other hand, the pcmQ gene may encode a MarR-type transcriptional regulator that could be involved in the expression of other pcm genes (277). Proteomic (277) and transcriptomic (48) results have shown that the pcmRST genes are induced not only when the G. metallireducens cells grow in the presence of 4-HBA but also when they are cultivated with benzoate.…”
Section: Gene Clusters For Degradation Of Aromatic Acidsmentioning
confidence: 99%
“…7). Notably, although PcmR would be the FAD-containing subunit of 4-hydroxybenzoyl-CoA reductase, it does not contain the [4Fe-4S] cluster binding loop, which suggests a mode of electron transfer to the substrate that is different from that postulated for the classical 4-hydroxybenzoyl-CoA reductases from facultative anaerobes (277). The deduced pcmUVWX gene products show similarities to proteins involved in the maturation of molybdenum-containing enzymes and are proposed to play a role in the molybdenum cofactor assembly of 4-hydroxybenzoyl-CoA reductase.…”
Section: Gene Clusters For Degradation Of Aromatic Acidsmentioning
confidence: 99%
See 3 more Smart Citations